Pretreatment with nitrous oxide enhances induction of anesthesia with sevoflurane: A randomized controlled trial - Argyro Fassoulaki; Chryssoula Staikou (Wolters Kluwer Medknow Publications, 2015)
Background: Inhalation anesthesia with sevoflurane may be enhanced by several drugs or techniques. The aim of the present study was to investigate the effect of nitrous oxide (N2O) pretreatment on the speed of anesthesia induction with sevoflurane. Materials and Methods: Eighty patients scheduled for hysteroscopy under general anesthesia were randomly assigned to inhale for 10 min before induction 50% N2O in oxygen or air via a facemask. Anesthesia was induced with 7-8% sevoflurane in oxygen via a facemask. Bispectral index (BIS), end-tidal carbon dioxide (EtCO2) tidal volume, respiratory rate, oxygen saturation (SpO2), and heart rate were recorded every minute during the 10 min pretreatment periods and every 30 s during the first 300 s of induction with sevoflurane. During induction of anesthesia inspired and end-tidal sevoflurane concentrations were also recorded. Results: During the 10 min of inspired 50% N2O or air BIS, EtCO2, tidal volume, respiratory rate and heart rate values did not differ between the two groups except for the SpO2, which was higher in the N2O group (P <0.001). During induction of anesthesia the N2O group exhibited lower BIS values (P = 0.001), being significant at 60-150 s (P <0.001, P <0.001, P = 0.002, P = 0.014) as well as at 270 s (P = 0.004). EtCO2and tidal volume were consistently lower in the N2O group (P = 0.001, P = 0.041 respectively) and respiratory rate was higher (P = 0.007). Conclusion: Our results show that pretreatment of the patients with 50% N2O for 10 min enhances the speed of induction with sevoflurane as assessed by the BIS monitoring.